Lawyer’s liability in negligence to third parties / Norlida A. Rani - A. Rani, Norlida (Faculty of Law, 1986)
English common law has formed part of the law in Malaysia particularly in the areas of Torts. The relevant provision for the reception of the law of England into this country is provided for under Section Civil Law Act 1957 (Revised 1972) Section 3 (1) (a) states that: Save so far as other provisions has been made or may hereafter be made by any written law in force in Malaysia, the Court shall (.a) in the West Malysia or any part thereof apply the Common Law of England and the rules of Equity as ii England on the 7th day of April 1956 The date, 7th April 1956 is important because only English common law and Equity as administered on that date in England is applicable.Uhder Section 3 (1) (b), the English law applicable in Sabah is the common law of England and the rules of Equity together with statutes of general applications as administered or in force in England on the 1st. day of December,1951